Linear functional equations involving finite substitutions - Bessenyei Mihály (Acta scientiarum mathematicarum, 2017)
In this paper, we study single-variable linear functional equations that involve one unknown function and a finite set of known functions forming a group under composition. The main results present the complete description of the solution set, and provide an alternative and effective approach for some known facts. In the proofs, the standard methods of Linear Algebra, of Group Theory, and the Axiom of Choice play a key role.